Family inclusion in mental health services: Reality or rhetoric? - Martin, R.; Ridley, S.; Gillieatt, Sue (Sage Publications Ltd., 2017)
Background: Contemporary mental health policies require family inclusion in the design, implementation and evaluation of services. Materials: This scoping review considers the factors in mental health practice which either mediate or promote family inclusion. A wide range of factors are reported to obstruct family inclusion, while a smaller number of studies report that meaningful family inclusion rests on a partnership approach which values the input of families and services users. Discussion: When it comes to family inclusion, there is a gap between policy and service delivery practice. Changes in service delivery attitudes, values and culture are necessary to meaningfully and systematically include families and service users.